Prevalence of Incarceration of Inguinal Hernia in Adults (Bangladesh Armed Forces Medical Journal, 2025)
Background: Incarceration of inguinal hernia refers to a condition in which a segment of the intra-abdominal content becomes trapped in the hernia sac, which can lead to complications such as bowel obstruction, strangulation, and tissue necrosis. Emergency surgical intervention involves higher complexity and risks compared to elective repairs. Therefore, carries a greater risk of post-operative complications and prolonged hospital admission. Research on the prevalence of incarceration of inguinal hernia in adults with associated risks can highlight opportunities for preventive measure and early intervention strategies. The objective of the study is to quantify how common incarcerated inguinal hernias are among adult populations in consideration of various risk factors. Methods: A descriptive cross-sectional study was conducted at the department of surgery, Combined Military Hospital, Rawalpindi, Pakistan from 22nd August 2024 to 21st September 2024 to explore the prevalence of incarceration among 100 adults, both men and women, who presented with incarcerated inguinal hernia. Data were collected purposively from hospital records using a pre-tested check list. Ethical issues were properly addressed. Statistical Package for Social Sciences (SPSS) version 25.0 was used to analyze data. The patients were grouped according to their age into following categories: the young adults (up to 30 years and 31 to 40 years), aged adults (41 to 50 years and 51 to 60 years), elderly adults (61 to 70 years followed by 71 years and above). Results: This study examined the demographics and potential risk factors for inguinal hernia. The sample included 67% men and 33% women, with an average age of 50.39 years. Hernia cases were most common among individuals aged 51-60 (32%) and those over 70 (24%), suggesting higher susceptibility in older adults. While BMI did not correlate significantly with hernia prevalence, 48% of cases fell within the normal BMI range. No significant association was found between gender or common comorbidities (constipation, 12%; haemorrhoids, 4%) and hernia risk, nor was there a notable connection with heavy weightlifting, which affected only 12% of the cases. Conclusion: A strong relation between age and incarceration rate of the adult patients who presented themselves with inguinal hernia.Bangladesh Armed Forces Med J Vol 57 No (2) December 2024 pp 14-20